2018
DOI: 10.1111/jmg.12302
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic control of staurolite–Al2SiO5 mineral assemblages: Implications for Barrovian and Buchan metamorphism

Abstract: The distribution and textural features of staurolite–Al2SiO5 mineral assemblages do not agree with predictions of current equilibrium phase diagrams. In contrast to abundant examples of Barrovian staurolite–kyanite–sillimanite sequences and Buchan‐type staurolite–andalusite–sillimanite sequences, there are few examples of staurolite–sillimanite sequences with neither kyanite nor andalusite anywhere in the sequence, despite the wide (~2.5 kbar) pressure interval in which they are predicted. Textural features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 92 publications
(210 reference statements)
0
21
0
Order By: Relevance
“…Several common reactions, such as St → Grt + Bt + ALS, or St + Chl → ALS + Bt, involve staurolite as reactant and produce an aluminosilicate (ALS) polymorph. Pattison and Spear (2018) noted that the width of zones of coexisting staurolite and andalusite in Buchantype sequences is much wider than predicted by equilibrium phase diagrams, which they attributed to disequilibrium processes related to sluggish dissolution of staurolite and the lack of a thermodynamic driving force for the conversion of staurolite to andalusite. Although the two samples from the staurolite (H30) and andalusite (H44) zones have different mineral assemblages, calculated equilibrium temperatures are similar.…”
Section: Assemblage Stability Diagramsmentioning
confidence: 98%
“…Several common reactions, such as St → Grt + Bt + ALS, or St + Chl → ALS + Bt, involve staurolite as reactant and produce an aluminosilicate (ALS) polymorph. Pattison and Spear (2018) noted that the width of zones of coexisting staurolite and andalusite in Buchantype sequences is much wider than predicted by equilibrium phase diagrams, which they attributed to disequilibrium processes related to sluggish dissolution of staurolite and the lack of a thermodynamic driving force for the conversion of staurolite to andalusite. Although the two samples from the staurolite (H30) and andalusite (H44) zones have different mineral assemblages, calculated equilibrium temperatures are similar.…”
Section: Assemblage Stability Diagramsmentioning
confidence: 98%
“…However, the peak assemblage also contains staurolite, which is not predicted to be stable along with kyanite in Figure 8a. Pattison and Spear (2018) have shown that the width of zones of coexisting staurolite and kyanite, in Barrovian sequences, is much wider than that predicted in equilibrium phase diagrams. They suggested that the unusual width of coexistence of staurolite and kyanite (seen as an extremely narrow field in Figure 8a) may be a result of a lack of thermodynamic driving force to convert staurolite to kyanite, sluggish dissolution of staurolite, or the absence of a fluid phase.…”
mentioning
confidence: 78%
“…Both Barrovian and Buchan facies series comprise the same three facies, i.e., greenschist facies, amphibolite facies, and granulite facies. Nevertheless, Barrovian-type metamorphism proceeds at higher pressures than Buchan-type metamorphism at the same temperatures (Zheng and Chen, 2017;Pattison and Spear, 2018), resulting in the formation of kyanite in the former but andalusite and sillimanite in the latter. Therefore, the differences in pressure and petrology are translated to the differences in metamorphic thermal gradients (Zheng and Chen, 2017;Zheng, 2021a) and metamorphic thermobaric ratios Johnson, 2019a, 2019b).…”
Section: Metamorphic Facies Seriesmentioning
confidence: 99%